Identity landscapes : contemplating place and the construction of self - Lyle, Ellyn (Brill | Sense, 2020)
"Beginning from the notion that self is constructed, contributors in Identity Landscapes: Contemplating Place and the Construction of Self are particularly interested in how relationships with place inform identity development. Locating identity inquiry in methodologies that encourage an explicit examination of self (e.g. autoethnography, self-study, autobiographical inquiry, a/r/tography, and reflexive inquiry), authors situate themselves epistemologically and geographically as they explore where place and identity converge. Through critical, qualitative, creative, and arts-integrated approaches, this collection aims to advance thought regarding the myriad ways that place informs identity development"--